Legal Certainty in Payment for Land Sale and Purchase Transactions: The Role of the Land Deed Official - Anak Agung Ayu Intan Puspadewi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study is motivated by the absence of explicit regulations governing payment procedures in land sale and purchase transactions in Indonesia. The transfer of land rights resulting from a sale and purchase has been regulated under the Basic Agrarian Law and the Government Regulation on Land Registration. These provisions stipulate that the transfer of land rights must be carried out through a deed made by a Land Deed Official (PPAT). Accordingly, a land sale and purchase must be evidenced by a deed drawn up by the PPAT. However, the provisions regarding payment mechanisms are entirely left to the agreement of the parties based on the principle of freedom of contract as stipulated in the Civil Code, as well as the customary law principle of land transactions, namely “clear and cash” (terang dan tunai). This condition potentially creates legal uncertainty, particularly concerning the timing of payment to establish valid proof that triggers the transfer of land rights. The research problems addressed in this study are: (1) how is the legal regulation of payment in land sale and purchase transactions in Indonesia; and (2) what is the role of the PPAT in ensuring legal certainty related to such payments.This research employs a normative legal method using statutory and conceptual approaches, analyzed qualitatively. The results indicate that there is no explicit regulation regarding payment methods, thus in practice, payment arrangements largely depend on the agreement of the parties and the prudential principle exercised by the PPAT. In practice, the PPAT plays a role in ensuring the fulfillment of the “clear and cash” principle and in clearly stating payment details within the deed. In conclusion, there is a need for guidelines or strengthened regulations to ensure legal certainty and protection in the payment aspect of land sale and purchase transactions.Keywords: Land Sale and Purchase, Legal Certainty, Payment, PPAT